Research on Laser Distance Measurement Technology for Remaining Volume of Large Open-pit Material Yard. Issue 2 (August 2020) - He, Hongwei; Zhai, Shaolei; Zeng, Shufan; Fu, Kunpeng; Ruan, Jun; Wang, Yuyuan
Abstract: In view of the problems of low volume calculation accuracy, long data acquisition period, and inability to uniformly measure and calculate the storage yard type when measuring the storage of large yards using volume and density conversion, a high-speed laser scanner, distance sensor, angle sensor, and pitch sensor are proposed Integrated technology, quickly obtain the three-dimensional coordinate data of the yard, and derive a unified three-dimensional coordinate solution algorithm, establish a three-dimensional coordinate system of the yard space to solve the three-dimensional coordinates of the yard, and accurately calculate the storage volume of the yard. At the same time, the system construction architecture, composition, data processing methods and issues to be considered are proposed. This method effectively solves the problems faced by the existing measurements in large yards, and improves the measurement efficiency, accuracy and safety. Under the test conditions, the absolute accuracy reaches 0.4%. Several project examples show that the method is simple, efficient and accurate. The ordinary measurement time of a 200m stockyard does not exceed 20mIn, and the repeated measurement error of the measurement volume is less than 0.7%. It has good application prospects and popularization value.